Pre-service Teachers’ Perceptions of Tutoring Program: Case Study of Teacher College Model in Mauritania - Leghdaf Abdellahi, Mohamed; Tadesse, Endale; Khalid, Sabika (Middle Eastern Journal of Research in Education and Social Sciences, 2020)
Purpose: The main objective of this study is to investigate the perceptions of pre-service teachers regarding their tutoring program at teacher college model in Mauritania. Approach/Methodology/Design: Explanatory Sequential design was adopted. Hence, a survey questionnaire and interviews were developed to gather data from 80 pre-service teachers, 20 in-service teachers, and 2 mentors. Findings: The findings of the study revealed that internship training has a significant impact on the development of pre-service teachers, but the teacher trainees did not get enough time for internship training sessions due to the workload of the theoretical courses. Mentors and management support were found insignificant to the development of teacher college model trainees. Practical Implications: The study provides a systematic evaluation of the current in-service teacher training programs. It reflects certain aspects of the status quo, and hence it will be useful for the concerned authorities in the field of teacher education. Originality/value: Teacher College Model has to adjust the levels of its tutoring where the study found that teacher trainees suffer the short-term practicum while they are complaining about the workload of coursework. Another way of the assessment regarding the tutoring program could be including observation. It is suggested that a qualitative study where researchers can spend more time at the teacher college model and with teaching staff observing the different aspects of the tutoring program.